Motivation, loyalty, and commitment as pioneers of brand communities - Cristancho Triana, Gerson Jaquin (2023)
Brand communities are social expressions around the preference and perceived satisfaction of consumption towards a brand, so the fondness for a football team is directly related to this social expression of consumption. This research aims to determine whether motivation, loyalty and the level of commitment are aspects that favor the interest towards the generation of brand communities in football teams. From a descriptive study with a quantitative approach a questionnaire was applied to 413 football fans, in order to know how the motivations, the degree of loyalty and commitment influence the interest in belonging to the brand community focused on the football team, for this an analysis of structural equations using the technique bootstraping was used. It was identified that extrinsic motivation directly influences interest towards the brand community, while intrinsic motivation indirectly influences inversely.